Senescence and Telomere Homeostasis Might Be Involved in Placenta Percreta—Preliminary Investigation. (August 2018) - Tzadikevitch Geffen, Keren; Gal, Hilah; Vainer, Ifat; Markovitch, Ofer; Amiel, Aliza; Krizhanovsky, Valery; Biron-Shental, Tal
Objective: Placenta percreta (PP) is an abnormal condition of trophoblast maturation and terminal differentiation through the uterine wall. We opted to study telomere homeostasis and senescence expression in trophoblasts from PP, the most severe subgroup of placenta accreta. Study Design: Paraffin-embedded placental biopsies from pregnancies with percreta and normal placentation, matched by gestational age at delivery, were assessed for telomere length, aggregates, and senescence-associated heterochromatin foci using quantitative fluorescence in situ hybridization. Cyclin-dependent kinase inhibitors p21, p15, p16, and the tumor suppressor protein p53, known senescence-related markers, were assessed using immunohistochemical staining. Results: Short telomeres were found more often in trophoblasts from the samples of PP (n = 9) compared to controls (n = 8; 54% ± 20% vs 2.3% ± 1.16%, respectively; P < .05). More cells with telomere aggregates (18.3% ± 6.9%) were observed in the PP than in the control group (4.8% ± 5.4%; P = .0005). The percentage of nucleic senescence-associated heterochromatin foci in the PP and control samples was similar (10.9% ± 10.4% vs 10.7% ± 15%, respectively; P = .97). Immunohistochemistry of senescence markers was expressed differently in PP compared to the controls: higher p15 expression (46.42% ± 15.2% vs 36.63% ± 12.2%, P = .004), higher p21 expression (59.8% ± 22.1% vs 47.5% ± 21.9%, P = .011), lower p16 expression (54.8% ± 26.3% vs 73.4% ± 18.9%, P = .000), and lower p53 expression (24.4% ± 33.8% vs 34% ± 14.4%, P = .000). Conclusion: Placenta percreta exhibits telomere alterations and changes in expression of several senescence markers. These might be related to altered trophoblast invasion maturation and placental detachment postpartum.